A new Herbal preparation with hypoglycemic effect used in treatment of Non Insulin Dependent Diabetes Mellitus [NIDDM] - Omar Ahmed Abass (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2012)
Highly qualified herbal mixture prepared from; Artemisia herba Alba [aerial parts], Lupinus albus [fruits], Trigonella foenum-graecum [fruits], and Nigella sativa [fruits], in a proportion of [0.25 part: 0.25 part: 0.25 part: 1 part], mechanically milled to a uniform mesh size and homogenously fill size "0" hard gelatin capsules weight ≈ 700 ±10 mg . Forty-one [NIDDM] patients use this mixture for one month in a dose of one capsule three times daily after food assigned Group B. Another Forty-one [NIDDM] patients assigned Group A, are using Metformin tablets 500 mg three times per day after food for one month. Pre- and post- treatment of fasting blood glucose levels of both Groups recorded on three days interval per week for one month, the monthly average counted and the results analyzed statistically to show significant lowering of blood glucose for both groups after treatment, with significant improvement of blood sugar by Herbal medicine compared to Metformin.